Impact of Work Value Affecting Employee Job Satisfaction for Improving Organizational Performance - Hery Winoto Tj (GoAcademica Research & Publishing, 2019)
Companies that want to compete in the global era will increase productivity and performance to maintain a competitive advantage. Therefore, the company must pay attention to physical, financial, marketing, and human resources. Humans, in this case, employees, are the most valuable assets for the long term. Therefore, the organization or company needs to pay more attention to its employees. The goal of this analysis is to illustrate the effect of job values on employee satisfaction. To boost the efficiency of a company. This study uses a qualitative method by using literature studies to collect issues that are relevant to the object of research. The results showed that work value has a strong correlation with employee performance satisfaction. Employees' work values ​​at work, which include independence, working conditions, recognition, relationship, achievement, and support, provide a clear understanding and understanding between employees and companies that do. Of course, it will affect the company's performance.